Pólya-type polynomial inequalities in Orlicz spaces and best local approximation - Cuenya, Hector Hugo (2012)
We obtain an extension of Pólya-type inequalities for univariate real polynomials in Orlicz spaces. We also give an application to a best local approximation problem.